Experimental study on estimating bare soil moisture content based on UAV multi-source remote sensing - Hongyan Yuan; Shiqi Liang; Yurong Gao; Yulu Gao; Xugang Lian (Geocarto International)
The focus of this paper is to measure the moisture content of bare soil using multi-source remote sensing with UAVs. A series of experiments were carried out indoors and outdoors by using thermal infrared and multi-spectral sensors carried by UAV. In the indoor experiment, the relationship between surface spectral reflectance, thermal infrared surface temperature, and soil moisture content was analyzed, and the corresponding inversion model was constructed. The inversion effect was the most effective when the soil bulk density was high and the soil depth was 4–5 cm. In the outdoor experiment, the flight height of the UAV was 83 m and 108 m for thermal infrared and multi-spectral image acquisition, respectively. When the in situ average soil bulk density was 1.366 g/cm3, the moisture content at 3 cm and 6 cm was measured by temperature hygrometer, and it was found that the inversion model at 6 cm depth was better.